Technical report: analysis of percentage vehicles using lagrange interpolating method / Nurul Ain Nordin, Norfatin Mohamad and Zurdia Atirah Mastika Zaini - Nordin, Nurul Ain; Mohamad, Norfatin; Mastika Zaini, Zurdia Atirah (2016)
In determining an efficient traffic flows, the factors that bring about to this issue classified into the road, human behavior, vehicles and modernization of the area. the country of Wellington, New Zealand is one of the world worst areas that reported confronting traffic jammed particularly in the morning has been choose as our location study. This study focus on the increment number of vehicles that cause traffic jammed to occur. Disappointment methodology advancement arranging road structure as per the expanding in the quantity of vehicles cause unpredictability in taking care of the issues. A method for expanding pattern of the quantity of vehicles which have been used is Lagrange interpolating method. This method is able to assess the number of vehicles for any time during the year 2014. And at the end of the study, a comparison is made between the actual data and the data expected to see the level of accuracy.